A systematic sample of 10% of archaeological field reports published in samla.raa.se respository in 2018 - Huvila, Isto (Uppsala University, 2021)
A list of references (title, author(s) and URI) in a spreadsheet document to a set of archaeological field reports available (as of 02/2021) in the digital repository samla.raa.se produced by the Swedish National Beritage Board.

The dataset was originally published in DiVA and moved to SND in 2024.

A list of references (title, author(s) and URI) in a spreadsheet document to a set of archaeological field reports available (as of 02/2021) in the digital repository samla.raa.se produced by the Swedish National Beritage Board.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
A systematic sample of 10% of archaeological field reports published in samla.raa.se respository in 2018
Keywords: field reports; field reports; archaeological reports; archaeological reports; Library and Information Science; Library and Information Science; Archaeology; Arkeologi; Information Studies; Biblioteks- och informationsvetenskap